Dealing with Demography. Immigration Restrictions in the United States c. 1880-1930 and the Literature of Exclusion - Redvaldsen, David (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2026)
The article investigates immigration restrictions in the United States circa 1880 to 1930. The emphasis is on the rhetoric and arguments utilized by supporters of limiting the intake. In the time period, immigrants from southern and eastern Europe grew as a proportion of the total. The anticipated resulting demographic change was worrying to traditionalist Americans and to the labour movement. Yet their country had always progressed through arrivals from overseas. How could they formulate mechanisms of exclusion which distinguished between people who were similar to themselves and those who brought something new? The racist conservationist Madison Grant drew upon anthropology and history for his contention that Americans were a great fusion of pioneers from northern Europe. The historian and journalist Lothrop Stoddard continued this line of reasoning. Both were organized supporters of eugenics, a doctrine used to ‘fine-tune’ racist discourses. However, eugenics was only a factor in the last two decades of the period. The labour movement and others had been clamouring for immigration restrictions long before that, roused to action especially by the arrival of Chinese workers. The pamphlet Meat vs. Rice by American Federation of Labor leader Samuel Gompers and Herman Gutstadt, originally published in 1902, applied crude racism to limit competition from such entrants in the job market. A dividing line was drawn between those who could become American and those who could not, buttressed by the Naturalization Law of 1870 and the Chinese Exclusion Acts of 1882 and 1902. The negative contentions against immigrants from less familiar places had significant influence on the Immigration Act of 1924. The article argues that Yankee intellectuals often had a conception of America as a British republic, in which related peoples were assimilable and valuable too.